Utilization of Hand Puppets from Used Socks and Let's Read Application as Learning Media to Improve Students’ Story-Telling Skills - Rabiatul Adawiyah Siregar; Ikhwanuddin Nasution; Pardi Pardi (STAI Hubbulwathan Duri, 2022)
This research aims at describing the utilization of hand puppets made from used socks adn Let’s Read Application as a storytelling medium in improving the speaking skills of the students at Faculty of Teacher Training and Education (FKIP) Al Washliyah Univeristy (Univa), Medan. This study also aims to 1) produce the benefits of hand puppets from used socks and the Let's Read application as learning media, 2) test the feasibility of the learning media, and 3) test the effectiveness of the media. This study uses the Research and Development (RD) ADDIE model. The results show that the feasibility test result conducted by the material validator got an average of 87.5% and media experts got an average of 96.67% with very decent criteria. The limited-scale effectiveness tests of hand puppets made from used socks as a learning medium for the students of FKIP Univa Medan in the 2020-2021 academic year result in an average pre-test score of 41 and an average post-test score of 78. The Hand puppets and Let's Read application are effective to be used in the speaking skills course with t-count of 3,791 and t-table of 2,021. The N-gain calculation data is 0.43. It means that hand puppets made from used socks and the Let's Read application are feasible and effective to be used as learning media for storytelling in the speaking skills course. Students make recordings of storytelling using the hand puppets to display on YouTube. The media can be developed as one of the Indonesian language learning media so that students' understanding and Indonesian language skills increase.